2016
DOI: 10.1021/acs.energyfuels.6b00338
|View full text |Cite
|
Sign up to set email alerts
|

A pH-Resolved View of the Low Salinity Effect in Sandstone Reservoirs

Abstract: Core plug and field tests have shown that significantly more oil can be produced from sandstone reservoirs when the water that is injected to maintain pressure in the reservoir has lower salinity than regular seawater. We investigated the adhesion between functional groups known to dominate in crude oil and grains from reservoir sandstone as a function of pH and salinity. We used atomic force microscopy (AFM) in chemical force mapping mode, and we functionalized the AFM tips both with −CH 3 , to model adhesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 26 publications
2
15
1
Order By: Relevance
“…The observed increase in measured adhesion with increasing pH, however, is not in agreement with either CFM measurements performed on sandstone samples [33], nor with the studies on the adsorption of benzoic acid [37] and crude oil [38] by kaolinite. In the former experiments, the presence of organic groups in the surface was invoked to explain the results, so a direct comparison to the results shown here is not appropriate.…”
Section: Effect Of Ph In the Presence Of 0001 M Caclcontrasting
confidence: 90%
See 4 more Smart Citations
“…The observed increase in measured adhesion with increasing pH, however, is not in agreement with either CFM measurements performed on sandstone samples [33], nor with the studies on the adsorption of benzoic acid [37] and crude oil [38] by kaolinite. In the former experiments, the presence of organic groups in the surface was invoked to explain the results, so a direct comparison to the results shown here is not appropriate.…”
Section: Effect Of Ph In the Presence Of 0001 M Caclcontrasting
confidence: 90%
“…Austad et al have shown experimental data where an increase in the pH of the effluent solution is observed after injection of low salinity water [5]. In addition, Shi et al [33] observed a small decrease in the measured adhesion for CFM experiments performed on sandstone grains using -CH3 and -COOH functionalised AFM probes. For these reasons, it was decided to perform a series of experiments where the Ca 2+ solution composition was kept constant (at 0.001 M), but the pH was varied.…”
Section: Effect Of Cacl 2 Concentrationmentioning
confidence: 99%
See 3 more Smart Citations